Impact of sex differences on cardiac injury in critically ill patients with COVID-19 - Mathieu Jozwiak; Denis Doyen; Pierre Denormandie; Antoine Goury; Jonathan Marey; Frédéric Pène; Alain Cariou; Jean-Paul Mira; Jean Dellamonica; Lee S. Nguyen (Respiratory Research, 2023)
Abstract Background COVID-19 infections are associated with accrued inflammatory responses which may result in cardiac injury. Immune response to infection appears different between men and women, suggesting that COVID-19 patients’ outcomes may differ according to biological sex. However, the impact of biological sex on the occurrence of cardiac injury during intensive care unit (ICU) stay in COVID-19 patients remain unclear. Methods In this multicenter and prospective study, we included consecutive patients admitted to ICU for severe COVID-19 pneumonia, during the first two pandemic waves. Biological, electrocardiogram (ECG) and echocardiographic variables were collected on ICU admission. Cardiac injury was defined by increased troponin above 99th percentile of upper norm value and newly diagnosed ECG and/or echocardiographic abnormalities. The primary endpoint was the proportion of patients with cardiac injury during ICU stay according to biological sex. The impact of biological sex on other subsequent clinical outcomes was also evaluated. Results We included 198 patients with a median age of 66 (56–73) years, 147 (74%) patients were men and 51 (26%) were women. Overall, 119 (60%) patients had cardiac injury during ICU stay and the proportion of patients with cardiac injury during ICU stay was not different between men and women (60% vs. 61%, p = 1.00). Patients with cardiac injury during ICU stay showed more cardiovascular risk factors and chronic cardiac disease and had a higher ICU mortality rate. On ICU admission, they had a more marked lymphopenia (0.70 (0.40–0.80) vs. 0.80 (0.50–1.10) × 109/L, p < 0.01) and inflammation (C-Reactive Protein (155 (88–246) vs. 111 (62–192) mg/L, p = 0.03); D-Dimers (1293 (709–2523) vs. 900 (560–1813) µg/L, p = 0.03)). Plasmatic levels of inflammatory biomarkers on ICU admission correlated with SAPS-2 and SOFA scores but not with the different echocardiographic variables. Multivariate analysis confirmed cardiovascular risk factors (OR = 2.31; 95%CI (1.06–5.02), p = 0.03) and chronic cardiac disease (OR = 8.58; 95%CI (1.01–73.17), p = 0.04) were independently associated with the occurrence of cardiac injury during ICU stay, whereas biological sex (OR = 0.88; 95%CI (0.42–1.84), p = 0.73) was not. Biological sex had no impact on the occurrence during ICU stay of other clinical outcomes. Conclusions Most critically ill patients with COVID-19 were men and experienced cardiac injury during ICU stay. Nevertheless, biological sex had no impact on the occurrence of cardiac injury during ICU stay or on other clinical outcomes. Clinical trial registration NCT04335162